Vehicle Active Suspension Control using Multi-order PID Approach - Abdullah, M. A.; Ridzuan, M.R.; Ahmad, F.; Mohamed Jamil, F.; Ibrahim, M. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
This paper presents the comparison among passive, proportional-integral-differential (PID) and multi-order PID (MOPID) controlled active suspensions. The quarter car model is validated with previous experimental results. The active suspension control via simulation is performed at three different frequency regions which are below natural frequency of body, in between natural frequency of body and wheel and above natural frequency of wheel. The parameters are tuned and Dormand-Prince solver is used in the simulation. The MOPID controller produces good performance in controlling vertical body displacement and acceleration thus improve ride performance and comfort.